Enabling coexistence: Navigating predator‐induced regime shifts in human‐ocean systems. Issue 3 (11th May 2020) - Burt, Jenn M.; Wilson, Ḵii'iljuus Barbara J.; Malchoff, Tim; Mack, Wii‐tsts‐koom Anne; Davidson, Skil Hiilans Allan; Gitkinjuaas,; Salomon, Anne K.
Abstract: Rapid system‐wide changes triggered by predators can pose considerable challenges to people. In the Northeast Pacific, the recovery of sea otters Enhydra lutris following their extirpation due to the 18th and 19th century fur trade is driving a social‐ecological regime shift with profound implications. While the ecological consequences of this shift are well documented, very little research has examined the conditions that enable or constrain people's ability to adapt to the social, economic and cultural changes that transpire. Through a collaborative partnership and workshops with Indigenous knowledge holders spanning Alaska to British Columbia, along with quantitative and qualitative interviews in two Indigenous communities among the first to experience sea otter recovery, we examined people's perceptions of the social‐ecological conditions that affect their ability to adapt to these changes. We found that communities differed in their relative rankings of adaptation‐enabling conditions; however, the following four broad strategies were perceived as critical to improving coexistence with sea otters: (a) strengthening Indigenous governance and decision‐making authority; (b) promoting adaptive co‐management; (c) weaving Indigenous knowledge and Western science into management plans and (d) establishing learning platforms. Both communities also identified that increased livelihood options and financial assistance would not compensate for lost food security. Differences in enabling conditions and attitudes towards sea otters within and between communities can be attributed to the social‐ecological and political context in which sea otter recovery occurs. Our study suggests that enhancing Indigenous peoples' ability to adapt to predator‐induced regime shifts will require a transformation in current resource governance systems if we are to navigate towards an ecologically sustainable and socially just operating space. Overall, this work highlights the need for more Indigenous authority, knowledge and leadership in addressing predator‐induced regime shifts in coupled human‐ocean systems. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article